An Analysis of Students’ Online Learning Readiness in Indonesian Higher Education Post-COVID-19 Era: A Bibliometric Analysis and Systematic Review - Holikul Mubin (JEDMI: Journal of Education and Multidisciplinary Studies, 2025)
This study aims to analyze students’ readiness to engage in online learning in Indonesian higher education institutions during the post-COVID-19 era through a systematic review approach. Data were collected from 10 recent scientific articles published between 2023 and 2024 that met strict inclusion criteria. The analysis reveals that overall student readiness remains low, influenced by key factors such as limited access to technology, ineffective time management, low learning motivation, and unfavorable socioeconomic conditions. Additionally, psychological aspects of students, including emotional resilience and commitment to online learning, remain significant challenges. These findings highlight the need for integrated interventions to enhance digital literacy, technical support, as well as motivation and psychological readiness to make online learning more effective and sustainable in Indonesian higher education. The implications of this study are relevant for the development of adaptive higher education policies in the digital era.